RETRACTED: Efektivitas Pelaksanaan Kebijakan Pengurangan Penggunaan Kantong Plastik Di Kota Sukabumi - Ghifary Prinardi; Dian Purwanti; Yana Fajar Fy Basori (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
Following up on the review of articles published in the Professional Journal carefully, carefully, and considering the article entitled "Efektivitas Pelaksanaan Kebijakan Pengurangan Penggunaan Kantong Plastik Di Kota Sukabumi" Vol 9 No 1 (2022), DOI: https://doi.org/10.37676/professional.v9i1.2341 This paper was found to violate the Professional Journal Publication principles and has been withdrawn.This article has been published in the journal other and the letter of revocation of the article is attached in a PDF.The document and its contents have been removed from the Professional Journal, and reasonable efforts should be made to remove all references to this article.